Effects of endurance and high-intensity swimming exercise on the redox status of adolescent male and female swimmers - Kabasakalis, A.; Tsalis, G.; Zafrana, E.; Loupos, D.; Mougios, V. (Journal of Sports Sciences, 2014)
Throughout adolescence, swimmers begin to carry out demanding endurance and high-intensity training sets, the effect of which on redox status is largely unknown. The aim of the present study was to investigate the effects of 2000-m continuous swimming and 6 × 50-m maximal swimming on the redox status of adolescent swimmers. Fifteen male and 15 female swimmers, aged 14-18 years, provided blood samples before, immediately after, 1 h after, and 24 h after each exercise for the determination of redox status parameters. Oxidative damage was short-lived and manifest as increases in 8-hydroxy-2?-deoxyguanosine (8-OHdG) 1 h after high-intensity exercise (39%, P < 0.001) and in malondialdehyde immediately after both exercises (65%, P < 0.001). Alterations in antioxidant parameters were sustained during recovery: reduced glutathione decreased 24 h post-exercise (11%, P = 0.001), uric acid increased gradually after high-intensity exercise (29%, P < 0.001) and bilirubin peaked 24 h post-exercise (29%, P < 0.001). Males had higher 8-OHdG (49%, P = 0.001) and uric acid (29%, P < 0.001) concentrations than females. However, females showed higher values of malondialdehyde than males immediately post-exercise (30%, P = 0.039), despite lower pre-exercise values. In conclusion, both endurance and high-intensity exercise perturbed the redox balance without inducing prolonged oxidative damage in trained adolescent male and female swimmers. These swimming training trials were not found to be detrimental to the redox homeostasis of adolescents.